UJI PERFORMANCE MEJA GETAR SATU DERAJAT KEBEBASAN DENGAN METODE STFT - Jhon Malta (Jurnal Teknik Mesin, 2004)
In this research, it has been constructed a prototype of vertical shaking table, then its performance is tested and analyzed using the vibration signal processing. From this vibration signal can be acquainted the response of shaking table. In theoretical, a degree of freedom of vertical shaking table will have a perfectly stationary signal at all times of measuring, in the other side in experimental, the response of this shaking table has some frequencies. When this signal is processed by using Fast Fourier Transform or FFT, it will result the frequency spectrum which appear like a stationary signal at all times of measuring, so the time of vibration in time domain that will be undetected. To overcome the lack of FFT method, the vibration signal can be analyzed by using the Short Time Fourier Transform or STFT method. The results of this method can be viewed in spectrogram. By using this method, the vibration of shaking table can be depicted that occur at certain time.